Analysis of Risk Factors of HPS in Goods and Services Procurement for Jakarta Property Projects: Mitigasi Risiko HPS Berbasis Digital pada Pengadaan Proyek Properti - Gandhi, Iswara; Pontan, Darmawan; Inavonna, Inavonna; Kusumawati, Lili (Technomedia Journal, 2025)
The procurement of goods and services for property projects in Jakarta faces various challenges, primarily due to inaccuracies in the Self-Estimated Price (HPS), which lead to significant risks in cost, time, and quality. This study seeks to identify the dominant risk factors caused by HPS inaccuracies and propose effective strategies to mitigate their impact on property project procurement. The research uses the Analytical Hierarchy Process (AHP) method, with 54 respondents involved, to evaluate three key risk categories: cost, time, and quality, based on the effects of HPS inaccuracies. The study finds that these inaccuracies undermine budget efficiency, cause delays in procurement processes, and negatively impact the quality of goods or services received. Cost-related risks include document instability and unforeseen expenses, while time-related risks involve delays and frequent revisions of the HPS. Quality-related risks stem from the use of substandard materials and the failure to meet project specifications. To mitigate these risks, the study proposes updating the HPS with up-to-date market data, conducting regular price surveys, enhancing the skills of procurement teams, adopting digital technologies such as e-procurement systems, and improving supplier selection processes. These strategies aim to improve procurement efficiency, enhance project quality, and ensure cost-effectiveness, ultimately leading to better project outcomes.